Violence and the Displacement of Rail Workers of Altsasu-Alsasua in the Spanish Civil War and its Aftermath - Daniel Oviedo Silva; Esther Aldave Monreal; Juan C. García-Funes; Imanol Satrustegui Andres (Culture & History Digital Journal)
Forced displacements in the context of civil wars are intimately bound to the violent practices which accompany them. In the case of the Spanish Civil War and its aftermath, this relationship manifested itself in the massive flight of people who feared reprisals but also in displacements imposed by the authorities, or motivated by social exclusion. Studies relating to internal population movements within this context are rare, however. This work deals with the flight of the rail workers of Altsasu-Alsasua in the days following the coup of July 1936. After reviewing the literature on wartime displacements, both internationally and in Spain, the article uses 175 records created during the subsequent dismissal of rail workers in order to trace their wartime experiences. First, we examine the circumstances that produced early flights, which only make sense if we bear in mind the myriad experiences of socio-political conflict which preceded the war and heralded its beginning. Thereafter, the article maps the itineraries of those who abandoned the area. Finally, we examine the difficulties that marked the return home and the displacements many rail workers endured as part of the regime’s repressive policies.